Utility of Epilepsy Surgery in Survivors of Childhood Cancer - Siddiqui, Ayat; McGregor, Amy L.; Wheless, James W.; Klimo, Paul; Boop, Frederick A.; Khan, Raja B. (Neuropediatrics, 2021)
Resection of an epileptogenic focus improves seizure control in patients with drug-resistant epilepsy. There is little data available on usefulness of epilepsy surgery in childhood cancer survivors with drug-resistant epilepsy. To learn about seizure outcome after epilepsy surgery in childhood cancer survivors, we retrospectively reviewed charts of 42 children who were referred to an epilepsy center for surgical evaluation. Sixteen children (38%) were offered epilepsy surgery and 10 consented. Seizure outcome was classified based on International League Against Epilepsy outcome scale. All 10 children were having multiple seizures a month on therapeutic doses of three antiepilepsy drugs (AEDs). At a median follow-up of 5.6 years after epilepsy surgery, three children had class 1 outcome (no seizures), four had class 3 outcome (1–3 seizure days/year), and three had class 4 outcome (≥ 50% reduction in seizure frequency). One child was off AEDs, seven were on a single AED, and two were on three AEDs at their last follow-up. Epilepsy surgery had low morbidity and improved seizure control in childhood cancer survivors with drug-resistant epilepsy. Childhood cancer survivors with drug-resistant epilepsy should be referred to an epilepsy center for a higher level of care.
Keywords: refractory seizures; childhood cancer; epilepsy surgery; brain tumors